One view to the interaction in the social media - La Rosa Pinedo, Amaro (2016)
The article presents an exploratory approach on interaction in the social media. The author starts from one comparison between the street corner society of the 50’s and the contemporary interaction in social networking. Nature of interaction and some research results of this issue are described.